Preliminary study on potentials of pumice as the new material for floating devices and buoy products - Dony Adriansyah Nazaruddin; Arham Muchtar Achmad Nahar; Muhammad Muqtada Ali Khan (2014)
Pumice is a volcanic igneous rock which forms when magma with extremely high levels of water and gases is violently ejected from a volcano (in an explosive eruption), cools and depressurizes quickly and simultaneously above the ground. It is typically light colored, composed of volcanic glass, may or may not contain crystals, and commonly originated from high-silica (felsic) to intermediate magmas. Pumice commonly has vesicular or foamy (porous) texture and very low density, so it is enough for it to become the only rock that can float in water. In this study, pumice is for the first time exposed to see its potential as a new and alternative material to produce floating devices and buoy products. This rock is cut and shaped to become some products, such as surfing boards and lifebuoys. Different from other types of the same kind products that are mostly made of heavy materials, such as plastic (polyethylene), rubber, and fibreglass, pumice-based products are lighter, stronger, more buoyant, more durable, resistant, friendly to users and environmental as well as unique in appearance. Potential markets and customers of these products among others are sport and safety equipments traders and marine transportation (such as ship and ferry) companies. People can use pumice-based surfing boards personally for surfing activity and pumice-based lifebuoys for swimming especially for babies and kids.